Determinación de bacterias con potencial en biodegradación de nitrobenceno. - Peñafiel Jaramillo, María Fernanda (2020)
Biodegradable bacteria of aromatic compounds have been described for their ability to reduce pollution and help protect the environment against pollutants that attenuate against their environment, as well as acting synergistically to preserve the environment. The objective of this research was to select and identify the ideal strain with biodegradable nitrobenzene capacity. The selection of bacteria was classified by the morphological and biochemical characteristics, giving values of: (+) presence, (++) high presence, (-) absence. For the study of nitrobenzene degradation, a completely Randomized design (DCA), with 12 treatments in 3 repetitions with a positive control (RE4) and negative (E. Coli). The bioremediator bacteria with the greatest effects in the different biochemical tests (catalase, phosphatase, urease were Cha0, R4, PM 2/12, BO 3/8, PM 3/14, DICM GBF, DIC (1) TEMP, DIC Omg, CL0 Mg, DIC 4M, DIC 3 MBFA Growth by spectrophotometry at 600 nm confirmed the cellular increase in the DICmgBF and GL3 strains with an absorbance of 1.23 and 1.18, respectively.The phylogenetic groups are divided into 2 groups with evolutionary approaches. discharges the group is confirmed by, Cha0, R4, PM 2/12, BO 3/8, PM 3/14, DEC (1) TEMP, DICM CBF, DEC 3 MBF. Group 2 (B) is subdivided into B1 and B2 where the first group corresponds DIC 4M, DIC Omg, CLa Mg and GL1. and the second group GL3 and CP3 who were the strains that showed the highest growth in the culture medium at 600 ppm of nitrobenzene. Keywords: Bacteria, biodegradation, nitrobenzene, biochemical tests, spectrophotometry.